STAND-UP COMEDY: THE RELATION BETWEEN LANGUAGE AND CULTURE - Winarsih, Sri (Universitas Sam Ratulangi, 2020)
Stand-up comedy is a kind of entertainment which presents the art and speech competence. As a single performer on the stage without any supporting properties and partners, a comic is permitted to express any utterances and strived for making audiences laugh. So, language aspect is the most important element of this art in the form of utterances. Based on the theory that language both expresses and embodies cultural identity, concerning stand-up comedy a question then emerged; How are language and culture related by comicsâ€™ utterances? This study aims to describe the content and the way of the utterances expressed by comics in stand-up comedy; to reveal how language and culture are closely related. The data were collected from videos of Indonesian Stand-Up Comedy season 4 of the three winner comic performances. Through collecting, analyzing, presenting and interpreting the data as the steps of qualitative method employed, the finding shows that content of the utterances expressed by the comics represent their own culture included ethnicity and community which are related to the problem dealing with their social life. While, the way they express the utterances shows that there are striking differences among the three comics in uttering the sounds, words, sentences and gimmick. The content differences identify their cultural and social background. Stand-up comedy art reveals how the language closely related to the culture.Â Keywords: comic, culture, language, language identity, stand-up comedy